Requirements Engineering Quality: a Literature Review - Delima, Rosa; Azhari; Mustofa, Khabib (Prodi Pendidikan Teknik Informatika Universitas Pendidikan Ganesha, 2024)
Requirements Engineering Quality (REQ) has a large influence on the success of a software project. A systematic literature review (SLR) is conducted to get complete information about REQ. SLR reviewed 46 relevant publications from 2016 – 2022, sourced from three literature sources: Science Direct, Scopus, and IEEE. Based on the SLR, it is known that, generally, the artifacts processed for REQ are text requirements. The quality standards for REQ that are widely used are ISO/IEEE/IEC 29148 and IEEE 830, while the quality variables that are widely used are correctness, completeness, consistency, and defects/faults found in RE. A number of methods are used to perform automatic REQ. The most widely used method in publications is NLP. This is in line with most artifacts used in REQ, such as text requirements.